FISH PRODUCTION IN BASRAH CANAL AND SHATT AL-ARAB - Ali A. Jasim (Mesopotamia Journal of Agriculture)
Economical fish production in Basrah canal and Shatt Al-Arab River had been studied during October 2001 until September 2002, using same catch condition in the two environments. Study shows that catch efforts in Basrah canal equal to 0.26kg/h, while in shatt al-Arab was 0.47kg/h , and the annual production in Basrah canal was 13.68kg/hec/year and 21.47kg/hec/year in Shatt Al-Arab River. The total catch per year was 3.4 and 209.33 ton in Basrah canal and Shatt Al-Arab respectively.2991 fishes were caught which represented 44 species of them 22 mostly riverine species from Shatt Al-Arab river and 33 mostly marine species from Basrah canal.